GOVERNMENTAL FUNDING OF BIOMEDICAL RESEARCH IN THE UNITED STATES OF AMERICA, GREAT BRITAIN AND GERMANY - G. R. Khachatrtyan; O. Yu. Rebrova; V. V. Omelyanovskiy (Фармакоэкономика)
The description of the international practice of governmental funding of biomedical research is a significant aspect of development of the methodology for prioritization of funding of science (both basic and applied research) in the Russian Federation. The information about mechanisms of allocation of the governmental budget in biomedical research and about focus themes within biomedical research founded in open information sources is very limited.